1998
DOI: 10.1046/j.1365-2958.1998.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic characterization of benzylsuccinate synthase from Thauera aromatica: a new glycyl radical enzyme catalysing the first step in anaerobic toluene metabolism

Abstract: SummaryToluene is anoxically degraded to CO 2 by the denitrifying bacterium Thauera aromatica. The initial reaction in this pathway is the addition of fumarate to the methyl group of toluene, yielding benzylsuccinate as the first intermediate. We purified the enzyme catalysing this reaction, benzylsuccinate synthase (EC 4.1.99-), and studied its properties. The enzyme was highly oxygen sensitive and contained a redox-active flavin cofactor, but no iron centres. The native molecular mass was 220 kDa; four subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
345
1
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(372 citation statements)
references
References 37 publications
21
345
1
5
Order By: Relevance
“…The specific activity of the cell extract at 4 °C was 2.4 nmol/min/mg of protein, whereas at 30 °C the specific activity rose to 7.4 nmol/min/mg. This level of activity is similar to that reported in permeablized cells of Azoracus sp (18), and some 4 orders of magnitude higher than that reported for purified enzyme from T. aromatica (6). As judged by SDS-PAGE, the BSS α-subunit, a conspicuous band of M r 98,000, comprised about 3.5 % of the total proteins present in the cell free extract, which allows us to estimate k cat for BSS as approximately 0.11 s −1 at 4 °C and 0.35 s −1 at 30°C .…”
Section: Enzyme Assaysupporting
confidence: 88%
See 1 more Smart Citation
“…The specific activity of the cell extract at 4 °C was 2.4 nmol/min/mg of protein, whereas at 30 °C the specific activity rose to 7.4 nmol/min/mg. This level of activity is similar to that reported in permeablized cells of Azoracus sp (18), and some 4 orders of magnitude higher than that reported for purified enzyme from T. aromatica (6). As judged by SDS-PAGE, the BSS α-subunit, a conspicuous band of M r 98,000, comprised about 3.5 % of the total proteins present in the cell free extract, which allows us to estimate k cat for BSS as approximately 0.11 s −1 at 4 °C and 0.35 s −1 at 30°C .…”
Section: Enzyme Assaysupporting
confidence: 88%
“…EPR studies show that the resting enzyme harbors an organic radical similar to that observed in these enzymes (12)(13)(14). Like other glycyl radical enzymes, BSS is extremely oxygen sensitive, and exposure to air results in oxidative cleavage of the α subunit at the site of the presumed glycyl radical (6).…”
mentioning
confidence: 68%
“…The lowest level of identity (around 25%) was found with the well characterized PFLs PflB from E. coli (28) and C. pasteurianum (29). The highest degree of identity was obtained with PflD and f810 (41% and 37%, respectively), two Pfl homologues from E. coli with unknown functions (30), and the recently characterized enzyme involved in anaerobic toluene metabolism, benzylsuccinate synthase from Thauera aromatica (32% identity) (31) and TutD from Thauera sp. T1 (30% identity) (32).…”
Section: Resultsmentioning
confidence: 99%
“…Because of their oxygen-sensitive nature, GREs (11)(12)(13)(14) are proposed to have evolved before the appearance of oxygen in the atmosphere, and some speculate that class III RNR may be a truly ancient enzyme (15) because the ancestral RNR was likely involved in the conversion of RNA-to DNA-based life (16). Unlike RNR, which converts ribonucleotides to deoxyribonucleotides, PFL is a central metabolic enzyme that converts pyruvate and CoA to acetyl-CoA and formate (17).…”
mentioning
confidence: 99%